Bloat In Cattle - Max B. Irsik (EDIS)
VM-164, a 3-page fact sheet by M.B. Irsik, DVM, MAB, describes this abnormal accumulation of gas in ruminal forestomaches, clinical signs and differential diagnosis, frothy bloat, free gas bloat, incidence rates, and treatment and prognosis. Published by the UF Department of Veterinary Medicine -- Large Animal Clinical Sciences, March 2007.